Heterogeneous Preferential Attachment in Key Ethereum-Based Cryptoassets - De Collibus, Francesco Maria; Partida , Alberto; Piškorec , Matija; Tessone , Claudio J. (Frontiers in Physics, 2021)
In this paper we analyse the aggregated transaction networks of Ether (the native token in Ethereum) and the three most market-capitalised ERC-20 tokens in this platform at the time of writing: Binance, USDT and Chainlink. We analyse a comprehensive dataset from 2015 to 2020 (encompassing 87,780,546 nodes and 856,207,725 transactions) to understand the mechanism that drives their growth. In a seminal analysis, Kondor showed that during its first years, the aggregated Bitcoin transaction network grew following linear preferential attachment. For the Ethereum-based crypto-assets, we find that they present in general super-linear preferential attachment, i.e. the probability for a node to receive a new incoming link is proportional to k^α, where k is the node's degree. Specifically, we find an exponent α= 1.2 for Binance and Chainlink, for Ether α=1.1, and for USDT α=1.05. These results reveal few nodes become hubs rapidly. We then analyse wealth and degree correlation between tokens, since many nodes are active simultaneously in different networks. We conclude that, similarly to what happens in Bitcoin, "the rich indeed get richer" in Ethereum and related tokens as well, with wealth much more concentrated than in-degree and out-degree.